Kinase-mediated regulation of CryAB in muscle: from NUAK-dependent signaling to extracellular vesicle–driven amyloid secretion - Zhao, Ziwei (My University, 2025)
This thesis examines the role of NUAK kinase and CryAB in muscle proteostasis, addressing two key questions: (1) how does NUAK activity prevent protein aggregation, and (2) how do pathogenic CryAB alleles perturb proteostasis and promote amyloidogenesis? NUAK is a member of the AMP-activated protein kinase (AMPK) family, a conserved group of serine/threonine kinases with broad regulatory functions. To define the requirement for NUAK catalytic activity, I introduced point mutations at residues essential for phosphotransfer activity. Three independent loss-of-function alleles abolished enzymatic activity, leading to aberrant protein accumulation and progressive muscle degeneration, thereby establishing NUAK kinase activity as indispensable for muscle integrity. A prior yeast two-hybrid screen identified a physical interaction between NUAK and CryAB. To test whether CryAB is a direct substrate, I overexpressed NUAK, which enriched for phosphorylated CryAB species. Mass spectrometry of HA-tagged CryAB purified from muscle tissue identified serines 68 and 70 as phosphorylation targets. Alanine substitutions at these positions eliminated the modification, confirming NUAK- dependent regulation of CryAB through site-specific phosphorylation. The second half of this work delineates how CryAB pathogenic mutations perturb proteostasis and promote inclusion formation. Mutational analyses revealed two phenotypic classes: conventional aggregates and distinct inclusion-like structures. CryAB aggregates colocalized with canonical protein quality control markers including ubiquitin, p62/SQSTM1, and Bag3, consistent with impaired proteostasis. In contrast, CryAB inclusions were characterized by a unique association with desmin, extracellular vesicle (EV)-associated proteins (Rab27, CD81, Alix, TSG101), and localized preferentially at fiber peripheries. Transmission electron microscopy and Congo red staining confirmed that these inclusions are amyloidogenic. Preliminary genetic perturbations demonstrated that depletion of EV biogenesis components in CryAB mutant flies reduced both the size and abundance of amyloid inclusions, implicating EV pathways in their assembly. Collectively, these findings define NUAK as a critical kinase that maintains muscle proteostasis through phosphorylation of CryAB and establish that pathogenic CryAB mutations induce amyloidogenic inclusions whose formation is modulated by extracellular vesicle pathways. This work uncovers new mechanisms linking kinase signaling, molecular chaperones, and vesicle biology to amyloid pathology in muscle disease.
Keywords: Drosophila; Muscle; NUAK; CryAB; Amyloid; Extracellular vesicle